Design and fabrication of a 3D-printed drone-integrated winching system - William Crowe; Benicio Costales; Kyle Luthy (HardwareX)
Existing multi-rotor drone-based winching platforms can be expensive, complex, proprietary, and heavy. Here, an inexpensive, simple, effective, and lightweight drone winching platform named the CLARK-3 is described. This winching platform is suitable for payloads of up to 3 kg in its existing configuration and relies heavily on readily available standard parts and 3D printed components while being compatible with a variety of drone controllers. The CLARK-3 in its existing configuration weighs 0.8 kg, can hold up to 27 m of 130 N monofilament, and has a low power consumption at maximum load (∼16 W). Considerations were made during the design of the CLARK-3 to ensure field serviceability by reducing part count and simplifying disassembly.